SAT0152 Safety of Surgery in Patients Treated with Tocilizumab for Rheumatoid Arthritis: Data from The Regate Registry. (15th July 2016) - Locci, M.; Lukas, C.; Combe, B.; Banal, F.; Cormier, G.; Couret, M.; Dougados, M.; Flipo, R.-M.; Marcelli, C.; Pham, T.; Rist, S.; Solau Gervais, E.; et al.
Abstract : Background: Rheumatoid Arthritis (RA) patients have a higher risk of post-operative complications compared with the general population, especially considering the risk of infection. It remains unclear whether use of biological DMARDs, including Tocilizumab (TCZ), is an independent risk factor for post-operative complications.To date, there is no evidence pointing to delayed wound healing or increased risk of post-operative infection in patients receiving TCZ. Objectives: To evaluate safety and predictive factors of complications after surgery in rheumatoid arthritis patients receiving Tocilizumab in routine care. Methods: Patients treated with TCZ for RA included in the French REGATE registry were included if they underwent surgery. When TCZ was interrupted more than 12 weeks prior to surgery, patients were excluded. Post-operative complications were defined as an adverse event occurring in the 12 weeks after surgery. Frequency of post-surgery complications was collected and compared in patients with and without complications in order to identify factors associated with complications. A second analyze was achieved in patients with post-operative infection (local or general). Qualitative variables were compared by Fisher's test and quantitative variables were compared by the Mann-Whitney test. Results: Out of 1499 patients from the REGATE registry, a total of 167 patients underwent 175 surgical procedures: 103 orthopedic surgeries (58.9%) and 29 abdominal surgeries (16.6%). These patients were mainly women (84%), the mean age was 58.11±12.83 years, and the disease duration of 14.96±11.29 years. The mean delay between surgery and the last TCZ infusion was 4.94±1.74 weeks (median 4 weeks). Thirty-eight surgical procedures happened whereas the last TCZ infusion was less than 4 weeks ago. Fifteen patients experienced 15 complications (8.9%) with 10 severe infections, 1 intestinal obstruction, 1 RA flare, 1 delayed wound healing, 1 thromboembolic disorder and 1 hemorrhagic complication. Postoperative complications occurred after 7.8% of orthopedic surgeries (8 of 103) and 2.9% of abdominal surgeries (2 of 29). The 10 severe infections occurred mostly after orthopedic surgery (7/10). There was 7 surgical site infections (46.7%) and 3 general infections. In 5 patients, TCZ treatment was definitely stopped. In univariate analysis, leflunomide dose was significantly associated with postoperative complications (p=0.04). Steroids and previous Rituximab treatment in the year before surgery, tended to be associated with peri-operative complications (p=0.09 and 0.07 respectively). In multivariate analysis, considering patients with infectious complications, diabetes was significantly associated with an increased risk of infection (P=0.03, OR 8.01, 95%CI 1.29–49.71). Conclusions: In routine practice, the postoperative period in TCZ treated patients seem to be safe when TCZ is stopped 1 month before surgery. Diabetes was significantly associated with an increased risk of post-operative infection in RA patients treated with TCZ. Disclosure of Interest: None declared